(untitled) (Annals of Medical Research, 2021)
Aim: We aimed to determine the diagnostic value of blood parameters such as neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR) and mean platelet volume (MPV) values for sinonasal inverted papilloma (IP) and to investigate its relationship with severity of the disease.Material and Methods: In this retrospective study, 33 patients (22 males, 11 females; mean age 52.60±8.99 years) diagnosed with IP and 44 healthy individuals (25 males, 19 females; mean age 50.97±9.28 years) were included. NLR, PLR and MPV values of IP and control groups were calculated and compared statistically. In IP group, NLR values and stages of the disease in accordance with the Krouse Staging system were evaluated statistically. Results: NLR levels were significantly higher in the IP group than the control group. (Mean NLR: IP group= 2,484±1.132; Control group= 1.971±0.884; p=0.029). Lymphocyte, PLR and MPV values were not statistically significant between the two groups. A strong correlation was found between the NLR value and IP stages. Conclusion: In cases with inverted papilloma, the NLR value obtained by easy-to-perform and low-cost tests, can be used as a new inflammatory biomarker and to predict the severity of the disease. In order to confirm these findings, further studies with larger patient series are needed.